Thermal stability of composites of polyvinyl alcohol with nanocrystalline cellulose in its acid and neutralized forms. (November 2016) - Voronova, Marina I.; Surov, Oleg V.; Guseinov, Sabir S.; Zakharov, Anatoly G.
Abstract: Thermal stability of polyvinyl alcohol/cellulose nanocrystals composites has been studied. It has been shown that nanocrystalline cellulose in its acid form considerably enhances the thermal stability of the composites, while the neutral form of the nanocrystalline cellulose has little effect on the thermal stability of the composites. Highlights: PVA/CNCs composites were prepared by solution casting technique. Thermal stability of the PVA/CNCs composites was studied. CNCs in acid form considerably enhance the thermal stability of the composites. Neutralized CNCs have little effect on the thermal stability of the composites.